CREATED TEXTBOOKS ON THE SPECIALTY OF DOIRA IN THE NEW UZBEKISTAN AND THEIR ROLE IN INCREASING THE EFFECTIVENESS OF EDUCATION (Scientific journal of the Fergana State University, 2024)
This article describes the role of existing methodological literature in the development of the sphere of circle performance, their methodological analysis. At a time when the interest in the field of education and musical instruments is increasing day by day, the issue of methodical manuals and textbooks, which are being created to improve the efficiency of the field specialty, attracted our attention.